PERLINDUNGAN HUKUM TERHADAP MASYARAKAT GUARANI DALAM KASUS BIOPIRACY OLEH COCA-COLA BERDASARKAN PENGATURAN ACCESS AND BENEFIT SHARING DALAM CONVENTION ON BIOLOGICAL DIVERSITY (STEVIA STUDY CASE) - Layla W Puspita Sari (BELLI AC PACIS, 2020)
This research traces the identification of biopiracy conducted by Coca-cola Company toward stevia leaf in the jurisdiction of Brazil and Paraguay based on the provision of access and benefit sharing according to Convention on Biological Diversity. The type of research used is normative with prescriptive analytic to identifiy the conduct of biopiracy by Coca-cola Company to establish legal protection for Guarani People. The data used is secondary data that was collected by library reseacrh and with editing analysis style. The result of this research lead to the fact that the conduct of biopiracy did exist during the utilization of stevia by Coca-cola Company due to the absence of State’s Consent and no information delivered to the Guarani People. The locus of the conduct was involved two nations which impacted to the State’s obligation to protect the rights of its people. The fact that Brazil has already eancted the provision of access and benefit sharing but Paraguay has not due its unawareness that such commercial benefit may arise from the utilization of genetic resources take into account that if it requires for legal enforcement. The implementation of access and benefit sharing provision will ensure the legal protection for its people with optimal supervision.